Looking at candidates' Facebook profiles as a recruiter: Think Twice! - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2021)
In a research paper recently published in the prestigious Journal of Applied Pyschology, SMU Professor Filip Lievens and a team of researchers from the top universities in the United States and Australia revealed that it is not a good idea for recruiters to conduct social media checks on candidates.